PELATIHAN PEMBUATAN BAHAN AJAR MENGGUNAKAN APLIKASI MIND MAP BAGI GURU SMP 5 RAMBANG DANGKU MUARA ENIM - Firmansyah; Rusmin AR; Dian Eka Amrina (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
The results of a preliminary study conducted by the PPM team with the SMPN 5 Rambang Dangku group through interviews, obtained information that the majority of teachers were not familiar with the Xmind media referred to in the learning activities, this caused the media used by the class teachers were generally only limited to power points. Community service activities carried out to the teachers of Rambang Dangku Middle School 5 aims to provide an understanding of making learning media in the form of mindmaps using Xmind application assistance in class learning. The method and form of community service activities are guidance and training, with techniques: lectures that are varied with discussion and question and answer, assignments and demonstrations. To find out the success of this coaching and training tests and observation sheets were used. Knowledge and understanding of the use of this program can facilitate teachers in delivering learning material in class so that it is more interesting this can be seen from the pre test score of 63.18 and post score of 84.76 or an increase of 33.99%. Teachers can use application-assisted mind map media as an alternative teaching material that will be used in the learning process in class, because it has various features and convenience to provide explanations related to the teaching material being discussed.